Banking systems, central banks and international reserve accumulation in East Asian economies - Prakash Kumar Shrestha (Kiel Institute for the World Economy (IfW), 2012)
This paper examines changes in the balance sheets of the banking system in five East Asian economies which were affected by the 1997 Asian Crisis. These countries have persistently accumulated foreign currency reserves since the crisis. This paper estimates the impact of reserve accumulation on some important balance sheet variables such as liquid assets, credits and deposits of the banking system by applying panel data techniques. Estimates using data from Thailand, South Korea, Malaysia, Philippines and Indonesia show that reserve accumulation has a positive impact on the liquid assets and deposits of the banking system, but not on credit flows, after controlling for the effect of other potential variables.
Keywords: F31; E58; G21; 330; international reserves; central banks; banking systems and East Asian countries